Homeopathic medicinal products for preventing and treating acute respiratory tract infections in children - Hawke, Kate (Cochrane Database Syst Rev, 2018)
BACKGROUND: Acute respiratory tract infections (ARTIs) are common and may lead to complications. Most children experience between three and six ARTIs each year. Although these infections are self limiting, the symptoms can be distressing. Many treatments are used to control symptoms and shorten the duration of illness. They often have minimal benefit and may lead to adverse effects. Oral homeopathic medicinal products could play a role in the treatment of ARTIs for children if evidence for effectiveness is established. OBJECTIVES: To assess the effectiveness and safety of oral homeopathic medicinal products compared with placebo or conventional therapy to prevent and treat acute respiratory tract infections in children. SEARCH METHODS: We searched CENTRAL (2017, Issue 11), which contains the Cochrane Acute Respiratory Infections Specialised Register, MEDLINE (1946 to 27 November 2017), Embase (2010 to 27 November 2017), CINAHL (1981 to 27 November 2017), AMED (1985 to December 2014), CAMbase (searched 29 March 2018), British Homeopathic Library (searched 26 June 2013 ‐ no longer operating). We also searched the WHO ICTRP and ClinicalTrials.gov trials registers (29 March 2018), checked references, and contacted study authors to identify additional studies. SELECTION CRITERIA: Double‐blind, randomised controlled trials (RCTs) or double‐blind cluster‐RCTs comparing oral homeopathy medicinal products with identical placebo or self selected conventional treatments to prevent or treat ARTIs in children aged 0 to 16 years. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. MAIN RESULTS: We included eight RCTs of 1562 children receiving oral homeopathic medicinal products or a control treatment (placebo or conventional treatment) for upper respiratory tract infections (URTIs). Four treatment studies examined the effect on recovery from URTIs, and four studies investigated the effect on preventing URTIs after one to three months of treatment and followed up for the remainder of the year. Two treatment and two prevention studies involved homeopaths individualising treatment for children. The other studies used predetermined, non‐individualised treatments. All studies involved highly diluted homeopathic medicinal products. We found several key limitations to the included studies, in particular methodological inconsistencies and high attrition rates, failure to conduct intention‐to‐treat analysis, selective reporting, and apparent protocol deviations. We assessed three studies as at high risk of bias in at least one domain, and many had additional domains with unclear risk of bias. Three studies received funding from homeopathy manufacturers; one reported support from a non‐government organisation; two received government support; one was cosponsored by a university; and one did not report funding support. Methodological inconsistencies and significant clinical and statistical heterogeneity precluded robust quantitative meta‐analysis. Only four outcomes were common to more than one study and could be combined for analysis. Odds ratios (OR) were generally small with wide confidence intervals (CI), and the contributing studies found conflicting effects, so there was little certainty that the efficacy of the intervention could be ascertained. All studies assessed as at low risk of bias showed no benefit from oral homeopathic medicinal products; trials at uncertain and high risk of bias reported beneficial effects. We found low‐quality evidence that non‐individualised homeopathic medicinal products confer little preventive effect on ARTIs (OR 1.14, 95% CI 0.83 to 1.57). We found low‐quality evidence from two individualised prevention studies that homeopathy has little impact on the need for antibiotic usage (N = 369) (OR 0.79, 95% CI 0.35 to 1.76). We also assessed adverse events, hospitalisation rates and length of stay, days off school (or work for parents), and quality of life, but were not able to pool data from any of these secondary outcomes. There is insufficient evidence from two pooled individualised treatment studies (N = 155) to determine the effect of homeopathy on short‐term cure (OR 1.31, 95% CI 0.09 to 19.54; very low‐quality evidence) and long‐term cure rates (OR 1.01, 95% CI 0.10 to 9.96; very low‐quality evidence). Adverse events were reported inconsistently; however, serious events were not reported. One study found an increase in the occurrence of non‐severe adverse events in the treatment group. AUTHORS' CONCLUSIONS: Pooling of two prevention and two treatment studies did not show any benefit of homeopathic medicinal products compared to placebo on recurrence of ARTI or cure rates in children. We found no evidence to support the efficacy of homeopathic medicinal products for ARTIs in children. Adverse events were poorly reported, so conclusions about safety could not be drawn.